Contribution aux recherches sociales du Québec par une étude des variations régionales du nombre des vocations sacerdotales - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1957)
This study, one of the first ever published in that field of research, is devoted to the geography of sacerdotal vocations and is divided in two parts. The first part deals with the differential rates of sacerdotal vocations which characterize some regions of the Province of Québec. The author bas calculated « index numbers of sacerdotal fecundity  », and he studies the variability of these indexes within the limits of the diocese of Trois-Rivières. The data show that, before 1950, the St. Lawrence Lowlands region bas given a greater number of priests than the Valley of the St. Maurice River and a much greater number than the Laurentian Uplands. The second part of the article is more elaborated and treats of some « exterior » conditions which usually explain the number of vocations and justify the different contributions of various parts of the diocese. The various factors examined are demographic, familial, religious, economic, social, academic and historical. On this basis, the author formulates a series of observations which, taking into account the limited value of conclusions reached in social research, seem valuable for the understanding of the specific subject of this paper but also of many other problems concerning the social geography of the Province of Québec.